Physiological responses of postlarva black tiger prawn Penaeus monodon to combined effects of salinity and water soluble fraction of dubai crude oil - Warawan Sukrarurk (Chulalongkorn University, 2008)
Thesis (M.Sc.)--Chulalongkorn University, 1999